Social tensions/conflicts and their functions - Mishra, S.N.; Mishra, Sweta (2002)
Social tension may have existed in one form or other all along the human history, but the authors say, their definition as a phenomenon in social sciences and psycho-social analyses has been attempted in last century only. The article presents an indepth analysis of various social, psychological and historical factors working behind eruption and proliferation of social conflicts. it also analyses if the social chasms play some role in the gregarious life of men and societies. - Reproduced.
Keywords: Social conflicts